Community paralegals and the pursuit of justice - Maru, Vivek; Gauri, Varun, 1966- (Cambridge : Cambridge University Press, 2018)
The United Nations estimates that four billion people worldwide live outside the protection of the law. These people can be driven from their land, intimidated by violence, and excluded from society. This book is about community paralegals - sometimes called barefoot lawyers - who demystify law and empower people to advocate for themselves. These paralegals date back to 1950s South Africa and are active today in many countries, but their role has largely been ignored by researchers. Community Paralegals and the Pursuit of Justice is the first book on the subject. Focusing on paralegal movements in six countries, Vivek Maru, Varun Gauri, and their coauthors have collected rich, vivid stories of paralegals helping people to take on injustice, from domestic violence to unlawful mining to denial of wages. From these stories emerges evidence of what works and how. The insights in the book will be of immense value in the global fight for universal justice. This title is also available as Open Access.
Paralegal in Comparative Perspective : What Have We Learned Across These Six Countries? / Vivek Maru and Varun Gauri --'To Whom do the People Take Their Issues?' : The Contribution of Community-Based Paralegals to Access to Justice in South Africa / Jackie Dugard and Katherine Drage -- Community-Based Paralegalism in the Philippines : From Social Movements to Democratization / Jennifer Franco, Hector Soliman, and Maria Roda Cisnero -- Paralegalism in Indonesia : Balancing Relationships in the Shadow of the Law / Ward Berenschot and Taufik Rinaldi -- Kenya's Community-based Paralegals : A Tradition of Grassroots Legal Activism / H. Abigail Moy -- Squeezing Justice Out of a Broken System : Community Paralegals in Sierra Leone / Vivek Maru, Lyttelton Braima, and Gibrill Jalloh -- The Contributions of Community-based Paralegals in Delivering Access to Justice in Post-war Liberia / Peter Chapman and Chelsea Payne.
Title from publisher's bibliographic system (viewed on 11 Dec 2018).
Open Access title.
Keywords: Legal services -- Developing countries; Legal assistants -- Developing countries